The cost of action: large-scale, longitudinal quantitative research with AIDS-affected children in South Africa - Cluver, L.; Boyes, Mark; Bustamam, A.; Casale, M.; Henderson, K.; Kuo, C.; Lane, T.; Latif, S.; Latif, N.; Mauchline, K.; Meinck, F.; Moshabela, M.; et al. (HSRC Press, 2015)
This chapter reflects some of the key ethical quandaries that emerged from two longitudinal South African studies of the impacts of parental HIV/AIDS on children. The first was a four-year study of 1025 AIDS-orphaned, other-orphaned and non orphaned children to identify long-term impacts of orphanhood. In 2005 all children lived in the Cape Flats or on the streets of Cape Town, but by 2009 we followed them up into three provinces, and interviewed them in prisons and hospitals. The second study was a one-year national longitudinal study of 6000 children and 2600 of their primary caregivers – comparing children orphaned, living with sick parents and in healthy families to understand the impacts not just of death but also of parental illness on children’s health, psychological, sexual and educational outcomes. In 2009-10 this involved random systematic sampling of census enumeration areas in the Western Cape, KwaZulu-Natal and Mpumalanga, and in 2011-12 children were followed up in six provinces (Eastern Cape, Western Cape, Gauteng, Mpumalanga, Limpopo, Free State and North West), and also into Mozambique and Swaziland. The studies are explicitly aimed at helping to inform evidence-based policy-making, and are conducted in collaboration with the South African National Departments of Social Development, Health and Basic Education, with UNICEF, USAID, Save the Children and the National Action Committee for Children Affected by AIDS, and with the Universities of Oxford, KwaZulu-Natal, Cape Town and Witwatersrand. As the Principal Investigator of both studies, I was responsible for the studies overall, including the overarching ethical planning and conduct, and the day-to-day ethical decisions made by the project’s fifty fieldworkers, fifteen data capturers, ten managers and seven volunteers.